Application of Livestock Waste-Based Biogas Technology for Cattle Farming in Kondoano Village, Mowila District, South Konawe Regency - Sani, La Ode Arsad (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
The community service program by the KKN Tematik Team of Universitas Halu Oleo was carried out in Kondoano Village, Mowila District, South Konawe Regency. The aim of this activity was to enhance the knowledge and skills of farmers in utilizing Bali cattle waste through the application of biogas technology as a waste processing solution and alternative energy source. The implementation method began with a survey of the area to identify issues and potential, followed by technical guidance on biogas processing and activity evaluation. As a result, farmers gained knowledge and practical skills in converting livestock manure into biogas, which reduces environmental pollution and supports household energy needs. This activity involved the KKN Tematik team from the Faculty of Animal Husbandry, Universitas Halu Oleo, KKN students, and local farmers. This program successfully empowered the community to manage livestock waste independently into valuable and sustainable resources.